Postpartum Management of Women Begun on Levothyroxine during Pregnancy - Stagnaro-Green, Alex (Frontiers in Endocrinology, 2015)
During pregnancy, the thyroid gland must produce 50% more thyroid hormone to maintain the euthyroid state. Women with decreased thyroid reserve pre-conception, most typically due to Hashimoto’s thyroiditis, may develop hypothyroidism during pregnancy. Data over the last twenty years have reported a strong association between subclinical hypothyroidism and adverse maternal/fetal events. As a result of this association, an increasing number of women are being screened for thyroid disease either pre-conception or at the first prenatal visit. Consequently, an ever increasing number of women are being initiated on levothyroxine for the first time during pregnancy. At present, there are very limited guidelines related to the management of the thyroid disease in these women postpartum. Based on an understanding of the physiology of thyroid gland during pregnancy and postpartum, and the personal clinical experience of the author, recommendations for the postpartum management of women who were started on levothyroxine during pregnancy are presented.